Mata Uang Digital (Cryptocurrency): Apakah Statusnya Memenuhi Kriteria Harta (Maal) dan Mata Uang Dalam Islam? - Fauzi, Muhammad; Kusnadi, Kusnadi; Musdizal, Musdizal; Rafzan, Rafzan (Fakultas Syariah IAIN Kerinci, 2022)
This study aims to determine whether Cryptocurrency status can meet the criteria of wealth/property (Maal) and currency in Islam. This is based on the fact that the issue of Cryptocurrency as Maal and money in Islam has attracted attention from various parties. Cryptocurrency is a digital/virtual currency, with a decentralized system using peer-to-peer (Blockchain) technology without being regulated and issued by a third party. In contrast to fiat currency in physical form (banknotes and coins) and non-physical fiat currency (demand) which is centralized/regulated and issued by third parties. This research was conducted using the Literature Review approach. This research shows that Cryptocurrency status can meet the criteria of Maal and currency in Islam has not yet seen a thread, because from various parties there are still differences of opinion, there are cons group opinions;, netral groups opinions;, and there are also pros groups opinions;. Finally, this area is open for future research as many issues remain unresolved and more concrete work is needed.